Territorial rights and colonial wrongs. (23rd September 2020) - Ferguson, Benjamin; Veneziani, Roberto
Abstract: What is wrong with colonialism? The standard—albeit often implicit—answer to this question has been that colonialism was wrong because it violated the territorial rights of indigenous peoples, where territorial rights were grounded on acquisition theories. Recently, the standard view has come under attack: according to critics, acquisition based accounts do not provide solid theoretical grounds to condemn colonial relations. Indeed, historically they were used to justify colonialism. Various alternative accounts of the wrong of colonialism have been developed. According to some, colonialism involved a violation of territorial rights grounded on legitimate state theory. Others reject all explanations of colonialism's wrongfulness based on territorial rights, and argue that colonial practices were wrong because they departed from ideals of economic, social, and political association. In this article, we articulate and defend the standard view against critics: colonialism involved a procedural wrong; this wrong is not the violation of standards of equality and reciprocity, but the violation of territorial rights; and the best foundation for such territorial rights is acquisition based, not legitimacy based. We argue that this issue is not just of historical interest, it has relevant implications for the normative evaluation of contemporary inequalities.